Aspek Humor dalam Syair Tertawa Sekali Karya Abu Muhammad Perak - Iik Idayanti; Muhammad Kafrawi; Nadila Mudea; Sunengko; Yulia Nelfita (Fakultas Bahasa Seni dan Budaya, 2026)
This study examines the humorous aspects in Syair Tertawa Sekali by Abu Muhammad Hasan Perak, a Malay syair written in Jawi script in 1926 and published in Singapore in 1927. The text tells the story of a contest of sign-language knowledge between a professor sent by the King of Spain and Khadam, a servant of the King of England. Although Khadam is ultimately praised for his intelligence, he later reveals that his answers were not based on scholarly knowledge, but on coincidence and simple reasoning. This narrative provides an important basis for understanding how humor is constructed in classical Malay literature. The study aims to identify and explain the humorous aspects found in the text. It employs a descriptive qualitative method using library research, with bisociation theory as the main analytical framework. The findings show that humor in Syair Tertawa Sekali emerges from two main narrative incongruities that create comic effects through gaps between expectation and meaning. The discussion further indicates that the text presents several types of humor, namely critical humor, riddle-based humor, and personal humor. It can be concluded that humor in this work is produced through narrative tension, interpretive contrast, and the clever use of misunderstanding, which together reinforce the literary and cultural value of the text.